Surgical treatment of oligometastatic non-small cell lung cancer - Pfannschmidt, Joachim; Dienemann, Hendrik (Lung cancer, 2010)
Patients with stage IV metastatic non-small cell lung cancer (NSCLC) are generally believed to have an incurable disease. Patients with oligometastatic disease represent a distinct subset of patients among those with metastatic disease. There is evidence that these patients have synchronous or metachronous satellite nodules in different pulmonary lobes or have solitary extrapulmonary metastases. In these cases, evidence has shown that surgical resection may provide patients with survival benefit. This article discusses the biology of the oligometastatic state in patients with lung cancer and the selection of patients for surgery, as well as the prognostic factors that influence survival of the patient. To properly select patients for an aggressive local treatment regime, accurate clinical staging is of prime importance. The use of FDG-PET should be considered for restaging if oligometastatic disease is suspected based on a patient's CT scan. A limitation of retrospective clinical studies for oligometastatic disease is that it is difficult to summarize and evaluate the available evidence for the effectiveness of surgical resection due to selection bias, and to a high degree of variability among different clinical studies. Nevertheless, we can certainly learn from the clinical experience acquired from retrospective case series to identify prognostic factors. Following surgical resection, the overall 5-year actuarial survival rate is about 28% for patients with satellite nodules and 21% for patients with ipsilateral nodules. Patients with resected brain metastasis achieve 5-year survival rates between 11% and 30%, and those with adrenalectomy for adrenal metastasis achieve 5-year survival rates of 26%.
Gesehen am 02.05.2023